043 Neurological manifestations in rheumatological disease: a case series I. (23rd August 2021) - Manus, Eileen JMc; White, Douglas; Doube, Alan; Schepel, Jan; Phillips, Matthew; Solanki, Kamal
Abstract : Objective: Rheumatology encompasses a broad range of multisystemic, autoimmune and inflammatory disorders. Neurological manifestations of these diseases are not uncommon. Neurological findings may predate rheumatological findings or may emerge months to years post initial diagnosis. Rheumatological diseases presenting as neurological syndromes can cause diagnostic challenges. Methods/Results: We present a range of rheumatological cases with unusual neurological presentations that demonstrate this point including; C2-C3 facet arthropathy in Diffuse Scleroderma, Granulomatosis with polyangiitis manifesting with craniofacial involvement, pseudo vasculitis associated cerebrovascular events, SAPHO syndrome with a thoracic syrinx, Neuro- Bechet's vasculitis with tumour-like CNS lesions, Platybasia in Paget's disease and others. Conclusions: Familiarity with the neurological manifestations of rheumatologic diseases is important for both rapid diagnosis and appropriate intervention.